2018
DOI: 10.1371/journal.pone.0194686
|View full text |Cite
|
Sign up to set email alerts
|

Expand your body when you look at yourself: The role of the posture in a mirror exposure task

Abstract: Mirror exposure (ME) is one of the main components of the treatment of patients with eating disorders symptomatology and it has shown its effectiveness in improving several outcomes (e.g., body dissatisfaction). However, the study as to what body posture should be adopted to maximize its effectiveness has been neglected. From embodied cognition and emotion theories, the adoption of an expansive (vs. contractive) body posture has been associated with positive changes in cognitive and emotional responses. The ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
1
8
0
1
Order By: Relevance
“… Miragall et al (2018) stated that “women in the expansive condition showed higher positive emotions after the mirror exposure task” (p. 1, Abstract), suggesting that poses may affect emotions in this study. However, this is only partially true: In fact, women who had adopted HPPs afterwards reported more positive emotions than women who had adopted LPPs, but both groups showed a decrease in positive emotions.…”
mentioning
confidence: 61%
See 2 more Smart Citations
“… Miragall et al (2018) stated that “women in the expansive condition showed higher positive emotions after the mirror exposure task” (p. 1, Abstract), suggesting that poses may affect emotions in this study. However, this is only partially true: In fact, women who had adopted HPPs afterwards reported more positive emotions than women who had adopted LPPs, but both groups showed a decrease in positive emotions.…”
mentioning
confidence: 61%
“…Further, LPPs elicited negative mood (Rossberg‐Gempton & Poole, 1993) and guilt (Rotella & Richeson, 2013). By contrast, various authors (Davis et al, 2017; Jackson, Nault, Smart Richman, LaBelle, & Rohleder, 2017; Miragall, Etchemendy, Cebolla, Rodriguez, Medrano, & Baños, 2018; 4 Saggese et al, 2018) found no effects of poses on emotions, social anxiety, or vitality, and Nielsen (2017) reported no difference in optimism between people adopting HPPs versus LPPs. Finally, in chronically powerless people, HPPs elicited more vengeance than LPPs (Strelan, Weick, & Vasiljevic, 2014).…”
Section: Effects On the Actormentioning
confidence: 97%
See 1 more Smart Citation
“…Tais relações podem ser bidirecionais, mas não foram encontrados ensaios clínicos que avaliassem o efeito na postura corporal após intervenções sobre as emoções, apenas o contrário: vários ensaios clínicos investigaram o efeito de intervenções sobre a postura corporal e seus efeitos sobre as emoções. Por exemplo, Miragall et al (2018) verificaram que quando as mulheres com insatisfação com suas imagens corporais adotavam uma postura propositalmente expansiva em frente ao espelho, melhoravam suas emoções positivas como autoconfiança e felicidade, enquanto as participantes que adotaram uma postura propositalmente em fechamento, apresentaram mais sentimentos de submissão e de insegurança. Veenstra et al (2017) também observaram que em uma postura propositalmente inclinada à frente, os participantes tiveram mais facilidade em se lembrar de eventos negativos do que em uma postura neutra ou ereta.…”
Section: Resultsunclassified
“…Although studies on the effectiveness of embodiment interventions in eating disorder populations remain scarce (Stinson, 2019), there is some evidence from nonclinical samples suggesting that they could be a valuable complement to CBT for AN. For example, Miragall et al (2018) found that women with high body dissatisfaction could benefit more from mirror exposure when they adopted an expansive, rather than a contracted bodily posture. Another study by Allen, Gervais, and Smith (2013) also showed that the adoption of expansive (vs. constrictive) postures was associated with less restrained eating among women with high body shape concerns.…”
Section: Introductionmentioning
confidence: 99%